Wewenang Jaksa Pengacara Negara Dalam Pengembalian Uang Pengganti Perkara Tindak Pidana Korupsi - Muhammad Setya Ady Syarifuddin (Universitas Sriwijaya, 2018)
Article of Law No. 31 of 1999 which was amended and Supplemented by Law No. 20 of 2001 concerning Eradication of Corruption Crime are explained that prosecutors as state lawyers can make civil claims to restore State financial losses. This type of research is juridical-normative research using a legal, conceptual, and case approach. The results of the analysis of researchers, that the duty of the Prosecutor is not only limited as a Public Prosecutor in criminal cases, in this case the Civil Prosecutor's Law also has the duty, authority and role as a State Attorney in terms of returning as much as possible in eradicating criminal acts of corruption. This is in accordance with the civil lawsuit filed by the Prosecutor in case No.24/Pdt.G/2008/PN.Kpj.